Incidence, kinetics, and risk factors for intra- and extracranial cerebral arteriopathies in a newborn sickle cell disease cohort early assessed by transcranial and cervical color Doppler ultrasound - Bernaudin, Françoise; Arnaud, Cécile; Kamdem, Annie; Hau, Isabelle; Madhi, Fouad; Jung, Camille; Epaud, Ralph; Verlhac, Suzanne (Frontiers in Neurology, 2022)
The risk of stroke in children with sickle cell disease (SCD) is detected by abnormal intracranial arterial time-averaged mean of maximum velocities (TAMVs ≥200 cm/s). Recently, extracranial internal carotid artery (eICA) arteriopathy has been reported, and a cross-sectional study showed that eICA-TAMVs ≥160 cm/s are significantly associated with eICA kinkings and stenosis. The cumulative incidence of and predictive risk factors for intracranial arteriopathy are well described in sickle cell anemia (SCA=SS/Sβ0) but are lacking for SC/Sβ+ children, as is the cumulative incidence of eICA arteriopathy. We report a prospective longitudinal cohort study including 493 children with SCD (398 SCA, 95 SC/Sβ+), all assessed by transcranial and cervical color Doppler ultrasound. Cerebral MRI/MRA data were available in 375 children with SCD and neck MRA in 365 children. eICA kinkings were defined as eICA tortuosities on neck MRA, with an internal acute angle between the two adjacent segments <90°. The median follow-up was 10.6 years. The cumulative incidence of kinkings was significantly lower in SC/Sβ+ children than in children with SCA, and no SC/Sβ+ child developed intra- or extracranial stenotic arteriopathy. The 10-year KM estimate of cumulative incidence (95% CI) for eICA-TAMVs ≥160 cm/s revealed its development in the 2nd year of life in children with SCA, reaching a plateau of 17.4% (13.2–21.6%) by about 10 years of age, while the plateau for eICA stenosis was 12.3% (8.3–16.3%). eICA assessment identified 13.5% (9.3–17.7%) patients at risk of stroke who were not detected by transcranial color Doppler ultrasound. We also show, for the first time, that in addition to a congenital origin, eICA kinkings sin patients with SCD can develop progressively with aging as a function of eICA-TAMVs, themselves related to anemia severity. Ongoing hydroxyurea treatment was significantly associated with a lower risk of abnormal intracranial arteriopathy and eICA kinkings. After adjustment with hydroxyurea, baseline low hemoglobin, high reticulocyte, and WBC counts remained independent risk factors for intracranial arteriopathy, while low hemoglobin and SEN β-haplotype number were independent risk factors for extracranial arteriopathy. The association between extracranial arteriopathy and SEN β-haplotype number suggested a genetic link between the ethnic origin and incidence of eICA kinkings. This prospective cohort study shows the importance of systematically assessing the eICA and of recording biological parameters during the 2nd year of life before any intensive therapy to predict the risk of cerebral arteriopathy and treat patients with severe baseline anemia.